Neuropathological Sequelae of Developmental Exposure to Antiepileptic and Anesthetic Drugs - Ikonomidou, Chrysanthy; Turski, Christopher A. (Frontiers in Neurology, 2012)
Glutamate (Glu) and aminobutyric acid (GABA) are major neurotransmitters in the mammalian brain which regulate brain development at molecular, cellular and systems level. Sedative, anesthetic and antiepileptic drugs interact with glutamate and GABA receptors to produce their desired effects. The question is posed whether such interference with glutamatergic and GABAergic neurotransmission may exert undesired, and perhaps even detrimental effects on human brain development. Preclinical research in rodents and non-human primates has provided extensive evidence that sedative, anesthetic and antiepileptic drugs can trigger suicide of neurons and oligodendroglia, suppress neurogenesis, and inhibit normal synapse development and sculpting. Behavioral correlates in rodents and non-human primates consist of long-lasting cognitive impairment. Retrospective clinical studies in humans exposed to anesthetics or antiepileptic drugs in utero, during infancy or early childhood have delivered conflicting but concerning results in terms of a correlation between drug exposure and impaired neurodevelopmental outcomes. Prospective studies are currently ongoing. This review provides a short overview of the current state of knowledge on this topic.